Self-Compassion Online: A Pilot Study of an Internet-Based Self-Compassion Cultivation Program for Psychology Trainees. - Finlay-Jones, Amy; Kane, Robert; Rees, Clare (John Wiley & Sons, 2016)
Objective: The current study sought to conduct a preliminary investigation of the effectiveness and feasibility of a novel, self-guided online self-compassion training for reducing psychological distress and increasing self-compassion and happiness among psychology trainees. Method: A 6-week online self-compassion cultivation program was developed and delivered to Australian psychology trainees (n = 37), and a pre-experimental repeated-measures design was used to collect change data on self-compassion, happiness, perceived stress, emotion regulation difficulties as well as symptoms of depression, anxiety, and stress. Results: Participants reported significant increases in self-compassion and happiness and significant decreases in depression, stress, and emotion regulation difficulties between pretest and posttest, with the majority of changes maintained at 3-month follow up. Conclusion:  This study provides preliminary evidence supporting the effectiveness and acceptability of online self-compassion training as a positive, integrated, and meaningful way of reducing distress and promoting self-compassion and happiness among trainee psychologists.